EFEKTIFITAS SENAM HAMIL TERHADAP TINGKAT NYERI PUNGGUNG IBU HAMIL TRIMESTER III DI DESA KAYEN: Effectiveness Of Pregnancy Exercise On The Level Of Back Pain In Trimester III Pregnant Women In Kayen Village - Yuanita Mega Kumala Mega (LPPM - STIKES Pemkab Jombang, 2022)
Pregnancy exercise is one of the prenatal services in the form of movement exercises, can increase comfort and can relieve back pain complaints in pregnant women. The purpose of this study was to determine the relationship between pregnancy exercise and back pain levels in third trimester pregnant women in Kayen Village, Kayen District Pati Regency. This type of research is an analytic survey and uses a cross sectional method with a population of 50 pregnant women. The sampling technique in this study was a total sampling of 28 pregnant women. The results of this study indicate that of the 28 respondents who did exercise regularly and did not experience pain there were 12 people (42.9%), respondents who did routine exercise who experienced mild pain there were 7 people (25.0%) while the respondents who did gymnastics 9 people (32.1%) were not routinely and experienced moderate pain (p value 0.000 <0.05).